Brain Injury and Neurodevelopmental Outcomes in Children Undergoing Surgery for Congenital Heart Disease - Reitz, Justus Gregor; Justus Liebig University Giessen (My University, 2024)
Background: Brain injury is commonly seen on magnetic resonance imaging in infants with complex congenital heart disease. The impact of perioperative brain injury on neurodevelopmental outcomes is not well understood. This study evaluates the association of brain injury and other markers on neurodevelopmental outcomes in patients undergoing surgery for congenital heart disease during infancy. Methods: Term newborns with cardiac surgery performed between 2008 and 2019 at a single tertiary center were identified from a clinical database. Patients who underwent both pre- and postoperative brain magnetic resonance imaging were included. Those with underlying genetic conditions were excluded. Brain injury was characterized using an MRI scoring system described by Andropoulos et al. Neurodevelopmental outcomes were assigned using the Pediatric Stroke Outcome Measure (PSOM) and Glasgow Outcome Scale Extended Pediatric Version (GOS-E). Independent risk factors for poor neurodevelopmental outcomes were determined by multivariable Cox regression. Results: A total of 122 patients were included in this study (n=42 with single ventricle physiology). Surgery was performed using CPB in 103 (84%) patients. New or progressive brain injury was noted on postoperative MRI in 69 patients (57%). A total of 101 patients (83%) had at least one neurodevelopmental assessment (median age 36, interquartile range 19-54 months) with an early neurodevelopmental assessment (5 - 24 months) performed in 95 children. Multivariable Cox regression analysis of early neurodevelopmental outcomes identified new stroke on postoperative MRI as an independent predictor of poor neurodevelopmental outcome. Postoperative peak lactate was an independent predictor of poor outcome assessed by PSOM and GOS-E at the most recent neurodevelopmental follow up. Conclusion: This study reveals that evidence of new stroke on MRI after congenital heart surgery is a predictor of poor neurodevelopmental outcomes in early childhood. Postoperative lactic acidosis is associated with poor neurodevelopmental outcome and may be a surrogate biomarker for ischemic brain injury.
Keywords: Brain Injury; Pediatric Cardiac Surgery; Congenital Heart Disease; Neurodevelopmental Outcome; ddc:610